Diversification Strategies of Indonesian Seaweed Commodities to Strengthen Markets, Competitiveness, and Economic Resilience of Coastal Communities - Tabrani Tabrani; Wisman Indra Angkasa; Dien Noviany Rahmatika; Fahmi Firmansyah; Teguh Budi Rahajo (PT. Publikasiku Academic Solution, 2022)
Background: This paper aims to study the potential, opportunities, problems, and strategies for diversifying seaweed commodities to strengthen markets, competitiveness, and economic resilience of coastal communities. Seaweed is an aquaculture product that can improve the people’s economic welfare, deploy many laborers, and even increase the country's foreign exchange. Aim: The potential for seaweed distribution in Indonesia is wide open for those naturally grown and cultivated in the sea. Method: There are good opportunities for the seaweed industry related to the potential for cultivation land, availability of raw materials, and demands for processed products. However, there are problems and challenges to the nation’s ability to export and compete for world market share to meet the world's seaweed needs. Findings: They include low quality and continuity of raw materials, provided capital, weak human and institutional resources, and seaweed products marketing strategies. There must be appropriate strategies for the diversification of Indonesian seaweed commodities for market strengthening, competitiveness, and economic resilience of coastal communities